(untitled) (Research, Society and Development, 2023)
Temporomandibular disorder (TMD) is considered the most constant chronic condition in the orofacial region. Psychological reasons such as anxiety and depression have been frequently associated with the etiology and continuity of TMD, with the main characteristic being a complex disorder of multifactorial origin. The objective of this research was to highlight the connection between temporomandibular joint disorders and existing psychological aspects. Thirty scientific studies in English and Portuguese were evaluated, which were directly related to the proposed theme. In this study, it can be concluded that there was a significant correlation proportionally between the severity of the TMD and the magnitude of the psychological factors, as well as the need for a detailed diagnosis, analyzing with a multidisciplinary team its real origin to obtain success in the treatment.